A Review of Global Health Competencies for Postgraduate Public Health Education - Sawleshwarkar, Shailendra; Negin, Joel (Frontiers in Public Health, 2017)
During the last decade, the literature about global health has grown exponentially. Academic institutions are also exploring the scope of their public health educational programs to meet the demand for a global health professional. This has become more relevant in the context of the sustainable development goals. There have been attempts to describe global health competencies for specific professional groups. The focus of these competencies has been variable with a variety of different themes being described ranging from globalization and healthcare, analysis and program management, equity and capacity strengthening. This review aims to describe global health competencies and attempts to distill common competency domains to assist in curriculum development and integration in postgraduate public health education programs. A literature search was conducted using relevant keywords with a focus on public health education. This resulted in identification of 13 articles that described global health competencies. All these articles were published between 2005 and 2015 with 6 from the USA, 2 each from Canada and Australia and 1 each from UK, Europe and Americas. A range of methods used to describe competency domains included literature review, interviews with experts and employers, surveys of staff and students and description or review of an academic program. Eleven competency domains were distilled from the selected articles. These competency domains primarily referred to three main aspects, one that focuses on burden of disease and the determinants of health. A second set focuses on core public health skills including policy development, analysis and program management. Another set of competency domains could be classified as ‘soft skills’ and includes collaboration, partnering, communication, professionalism, capacity building and political awareness. This review presents the landscape of defined global health competencies for postgraduate public health education. The discussion about use of ‘global health’,’ international health’, ‘global public health’ will continue and academic institutions need to explore ways to integrate these competencies in postgraduate public health programs. This is critical in the post-MDG era that we prepare global public health workforce for the challenges of improving health of the ‘global’ population in the context of sustainable development goals.